Penguatan Strategi Pembelajaran Kolaboratif dalam Pendidikan Agama Islam untuk Membentuk Kecerdasan Sosial Siswa - Muhammad Jitu; Ahmad Agil; Gusmaneli Gusmaneli (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the strengthening of collaborative learning strategies in Islamic Religious Education (PAI) to develop students' social intelligence. Collaborative learning is considered an effective approach to improving social skills and interactions among students, which are crucial in character development based on Islamic values. Through a literature review, this research analyzes various references discussing the basic concepts, implementation, and role of collaborative strategies in building social intelligence according to Islamic teachings. The findings indicate that collaborative learning strategies enhance students' communication skills, empathy, and social responsibility, while also reinforcing religious values in social life. However, the success of its implementation is influenced by supporting factors such as teacher support, learning facilities, as well as challenges like disparities in students' abilities and limited time. This research is expected to contribute to the development of collaborative-based learning methods in religious education in Indonesia.